Sounion Revisited: The Sanctuaries of Poseidon and Athena at Sounion in Attica - Gina Salapata (Les Carnets de l’ACoSt)
Gina Salapata reviews Zetta Theodoropoulou-Polychroniadis, Sounion Revisited: The Sanctuaries of Poseidon and Athena at Sounion in Attica. Oxford: Archaeopress Archaeology, 2015. ISBN 978-1-78491-154-6.